The role of sales promotion in improving the relation between price perception and system quality of SVOD platform on purchase intention - Lembana, Devi Angrahini Anni; Triyanti, Vivi; Wijaya, Jessica (International Journal Labs, 2024)
This study aims to explore how Vidio.com can increase the number of users who are interested in even considering using this platform in the midst of fierce competition in theSVOD market, especially in Indonesia. The study was conducted from April to June 2023 and data collection took 1 month using a questionnaire method, namely Google Form which were distributed online to target respondents. The purpose of this research is to influence perceived price and perceived system quality in shaping consumer interest in subscribing to the SVOD platform - with a study on the Vidio platform. The results of this study indicate that the three variables under investigation have a major impact on users' intentions to subscribe to the platform (i.e., make a purchase). The impact of moderators between independent variables on dependents, specifically the influence of sales promotion methods can not enhance the relation of perceived pricing and perceived quality on ehancing the intention to purchase. Therefore, Vidio needs to pay attention to the performance of its application such as the speed of responding when users access features, the level of application errors or loading levels when the show is played, and privacy security, especially for users' personal data in order to provide a good user experience so that it can increase their interest in using the platform's paid packages.